(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Reading is a habit where students learn, gain knowledge, and develop new skills. This research aimed to investigate the effectiveness of reading strategies on reading comprehension. The findings were that reading strategies had a positive effect on the students’ reading comprehension. The students had favourable attitudes towards skimming, scanning, making predictions and questioning and they could apply these strategies to their reading processes and they helped them to comprehend the text better.